World Bank Gender Transport Surveys : An Overview - Babinard, Julie (World Bank, Washington, DC, 2012)
Between 2008 and 2010 the transport sector initiated several country surveys to measure road transport needs and the constraints of both men and women, and more specifically how transport is facilitating or constraining access to resources, markets, and employment. These surveys were conducted as part of a lending operation or Economic Sector Work (ESW) with financial support from the Gender Action Plan (GAP), which seeks to advance women's economic empowerment and accelerate the implementation of the Millennium Development Goal 3 (MDG3), promoting gender equality and women's empowerment). A report that reviews the methodology used for each country GAP-funded survey, the design and content of the questionnaires and the likely effect on the analysis shows that women tend to have access to a wider range of social and economic opportunities when transportation is available, safe and secure. The main recommendation of the analysis is that a standardized approach should be promoted for collecting and evaluating gender data in transport and the possible creation of a questionnaire module to be easily adaptable for future surveys to collect and report gender-disaggregated data that can meaningfully inform transport policy. Substantial background work in the transport sector was done to develop a transport module to be used in nationally representative surveys. This work could be expanded upon to focus on gender and transportation.